2013
DOI: 10.3109/0142159x.2013.775413
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing learning approaches: Practical tips for students and teachers

Abstract: Practicing each of these approaches by students and teachers and applying them in day-to-day learning/teaching activities are recommended for optimum performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 34 publications
1
53
0
3
Order By: Relevance
“…This suggests that additional variables should be included in future studies. Second, previous research has shown that a student´s approach to learning may not be stable, changing in response to task characteristics, learning environments, or personal features (Aharony, 2006;Ahmed et al, 2012;Azer, Guerrero, & Walsh, 2013;García, Cueli, Rodríguez, Krawec, & González-Castro, 2015). It would be necessary to examine this component in a wider range of situations to better delimit its relationship with academic achievement; third, the results from the present study cannot provide evidence about the directionality of the relationship among variables.…”
Section: Limitationsmentioning
confidence: 99%
“…This suggests that additional variables should be included in future studies. Second, previous research has shown that a student´s approach to learning may not be stable, changing in response to task characteristics, learning environments, or personal features (Aharony, 2006;Ahmed et al, 2012;Azer, Guerrero, & Walsh, 2013;García, Cueli, Rodríguez, Krawec, & González-Castro, 2015). It would be necessary to examine this component in a wider range of situations to better delimit its relationship with academic achievement; third, the results from the present study cannot provide evidence about the directionality of the relationship among variables.…”
Section: Limitationsmentioning
confidence: 99%
“…Current literature reports about the lack of disciplines that not only get the themes in a practical perspective, but also involves data interpretation, problem solving, experimental design, scientific report writing and collaborative work, with critical analysis of primary results and possible errors (Coil, 2010;Azer, 2013). In the present work, the proposed Summer Course in Molecular Biology challenged the students from biomedicine and biology undergraduate courses to isolate and manipulate DNA from human blood samples.…”
Section: Resultsmentioning
confidence: 99%
“…Providing and recommending a wide variety of learning resources, to suit learners with diverse learning preferences, may help students gain a variety of perspectives, integrate information from several learning resources, and extend their own learning approaches (Azer et al, 2013;Choi-Lundberg et al, 2015). In the present study, as well as data from over 140,000 respondents on the VARK website, the kinaesthetic responses are the most frequent at 29% compared to 22-26% for V, A, and R (VARK Learn Limited, 2016).…”
Section: Discussionmentioning
confidence: 99%